NGAYAH: MODEL PENDIDIKAN KARAKTER BERBASIS KEARIFAN LOKAL (PERSPEKTIF KAJIAN SOSIOLOGI PENDIDIKAN) - I Made Legawa (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2014)
There are eighteen values adopted by the government to build character education. Building the character education with all its values, can be done through building social and cultural values around the learners. It is as a means of local wisdom based character education. One of the local wisdoms in Bali that has something to do with character education is “ngayah”. Concept of “ngayah” is relevant in process of educating character during the teaching-learning process. It brings up moral values that are related to character education values. This will get the students involved in learning activities, especially constructing their social experiences during classroom activities.